Efektivitas Penerapan Permainan Tradisional dalam Meningkatkan Motivasi Siswa pada Pembelajaran PJOK - Faradila, Esla Zahra; Ihsani, Hanipa; Sopiah, Rohaeti Nining; Syahidah, Shofiyyah Muna; Dealova, Zahra Khairul; Mulyana, Agus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Physical Education, Sports, and Health (PJOK) is a very important part of the school curriculum, it aims to improve physical fitness, improve motor skills, and maintain students' mental health. The purpose of this study is to analyze the role of game-based learning, especially in traditional games, to increase students' active participation in PJOK subjects in schools. The research method used in this study is literature review, where researchers examine and identify journals in a structured manner throughout the process by following established procedures. The search for journal articles obtained 10 articles from 2018 to 2024, by searching and reviewing journals, books and articles using the keywords games, learning, and PJOK. Searches for research articles that have been published on social media go through open access channels such as Google Scholar. Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The findings of this study are that game-based PJOK learning usually makes students more interested and more actively involved in lessons. This shows that game-based learning can play a significant role in increasing students' interest and participation in PJOK subjects. As a result, it is important to incorporate this approach into learning practices in schools to achieve PJOK goals and improve students' learning experiences